Dampak komunikasi dalam membangun hubungan positif antara guru dan siswa: Kajian sistematis literatur - Hidayat, Rahmat; Eliasa, Eva Imania (Jurnal Pendidik Indonesia, 2024)
Effective communication between teachers and students plays a crucial role in building positive relationships, which not only influence the classroom atmosphere but also directly impact the success of the learning process. This study employs a qualitative approach using the Systematic Literature Review method to analyze relevant literature. The literature was obtained from Google Scholar, selected based on the relevance of the titles and abstracts to the research theme. The findings indicate that effective communication between teachers and students can enhance students' self-confidence, learning motivation, and mutual respect, thereby creating a conducive learning environment. Conversely, ineffective communication may trigger conflicts, reduce learning enthusiasm, and lead to an unproductive classroom atmosphere, ultimately hindering the achievement of educational goals.